Determination of blue water footprint in forages crops from irrigation disctrict 017, Comarca Lagunera, Mexico - Ríos Flores, José Luis; Torres Moreno, Miriam; Castro Franco, Rafael; Torres Moreno, Marco Antonio; Ruiz Torres, José (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
The aim of this work was the determination of the blue water footprint in forage crops from DR-017 "Comarca Lagunera", México. By means of productivity and efficiency mathematical models were used to estimate the blue water footprint of forages crops. The results show that forages occupied 45% of the total agricultural area using 94,7% of groundwater, generating 33% of the Gross Value Production. Physical productivity rates were on average 252 L kg-1 (forage sorghum 181 L kg-1, forage oats 413 L kg-1 alfalfa L kg- 1). Income per m3 was US 0.04 m-3 on average (US 0.94 m-3 in forage maize, US 0.05 m-3 alfalfa forage). The social efficiency indicator showed in average 0.048 jobs per hectometer (0.037 jobs hm-3 in alfalfa and 0.076 jobs hm-3 in rye grass). Finally, under the same crop y market conditions the minimum amount for a viable operation (break-even point) was 39.02 t ha-1. In conclusion, the production of corn and sorghum forage in the region was highly efficient and productive compared to other forage crops which resulted in lower blue water footprint.